Factors affecting faculty conformity in South China universities - Xu, Chuang; Chang, Yuan-Cheng (Frontiers in Psychology, 2022)
Abstract Based on social contagion theory, this study examines the mediating role of formalization of organizational structure between organizational identification and faculty conformity. It also analyzes the moderating role of conflict management style between organizational identification and faculty conformity, and formalization of organizational structure and faculty conformity in universities in Hunan province,China. We conducted surveys and tested 1000 faculty members from four universities in Hunan and used the SPSS to analyze the data through descriptive analysis, analysis of variance, correlation analysis, and hierarchical multiple regression. We found that faculty members’ organizational identification had a positive effect on faculty conformity; formalization of organizational structure partially mediated the relationship between organizational identification and faculty conformity; and conflict management style positively moderated the relationship between organizational identification and faculty conformity and between formalization of organizational structure and faculty conformity. University administrators are often the initiators of conformity as they are responsible for formulating internal regulations. Therefore, they must monitor and coordinate workplace conflicts, resolve and guide faculty conformity, promote individual faculty members’ self-improvement, and foster steady organizational development.